Measuring clinical skills in agenda-mapping (EAGL-I). Issue 10 (October 2015) - Gobat, Nina; Kinnersley, Paul; Gregory, John W.; Pickles, Timothy; Hood, Kerenza; Robling, Michael
Highlights We developed EAGL-I, a measure of agenda-mapping for use in teaching and research. We demonstrate reliability and validity of EAGL-I scores. Higher EAGL-I scores predict greater likelihood that a patient will disclose their full agenda in a simulated environment.